A Portal to Browse Top Universities According to Your Preferences : Result - Meshram, Shravani; Tambakhe, Prathmesh; Gupta, Nidhi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Develop a platform that empowers students, educators, policymakers, and the public by offering insights into the educational landscape. This website will be user-friendly and informative, providing a comprehensive overview of universities based on statistical metrics, emphasizing data representation. Users can explore academic achievements through metrics such as pass rates, average GPA, and research output percentages. Additionally, the platform allows for easy comparisons between universities to help users assess each institution's strengths and weaknesses.
Keywords: University; Education; Platform; Portal; Information